Clinical cases of Darier-White follicular dyskeratosis - V.Ye. Tkach; M.S. Voloshynovych; S.M. Romanchuk; G.Ye. Girnyk; N.R. Matkovska; N.V. Kozak (Medičnì Perspektivi, 2022)
Follicular dyskeratosis (Darier-White disease) is a hereditary skin disease that is extremely rare in medical practice, so errors in its diagnosis can occur. It was first described in 1889 by two scientists (independently of each other), Ferdinand-Jean Darier and James White. The disease is inherited in an autosomal dominant pattern with variable gene penetrance. The main cause of this pathological process is a mutation of the ATP2A2 gene, located in the long arm of chromosome 12. Both men and women are affected with the same probability, but clinical manifestations are more severe in males. It appears, as a rule, at the age of 20; children under 10 rarely suffer from DAR; people who are over 30 years have very little chance of contracting this disease. Clinical manifestations slowly progress up to the age of 40-50, and gradually disappear in older age. Typical rashes are follicular papules, 0.2-0.5 cm in size, yellow-brown or dark brown in color, covered with dry or oily layers in the form of horny scales. On the surface layers, black dots are visible which are hair follicle funnels. Papules are rounded, dense, flat or spherical, initially isolated, eventually merging into plaques. They are mostly localized on the skin of the limbs, trunk, chest, in the interscapular area, large folds, less often on the neck, scalp, auricles, and in the ear canals. In 20-30 percent of patients, rashes are localized on the mucous membrane of the oral cavity next to the affected skin. More than 90 percent of patients have nail abnormalities, such as erythro- and leukonychia. Other possible manifestations are fragility, splinter hemorrhages, marked subungual hyperkeratosis, which can be observed on 2-3 nails or affect all nail plates. The dermatoscopy of skin lesions is characterized by the presence of several polygonal, branched, star-shaped or rounded-oval yellow-orange-brown lumps of various sizes, surrounded by a thin whitish halo and pink small-structured areas. The prognosis for recovery is not favorable, the treatment is ineffective. Two cases of Darier-White disease are described in this article.